2021
DOI: 10.3390/ani11061725
|View full text |Cite
|
Sign up to set email alerts
|

An Ethical Framework for the Use of Horses in Competitive Sport: Theory and Function

Abstract: Growing ethical concern about equestrian sport is reflected in publications by regulatory authorities, animal charities, and the lay press; and in government debate and social media. However, attempts by regulators and stakeholders to address ethical issues in equine sport have been discipline specific and ad hoc. Ethical frameworks can help stakeholders to make contextual decisions about what should or should not be done in a particular situation. However, when existing animal welfare frameworks and existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“…It could be noted that in the literature, there is not always a clear correlation between stressors and poor welfare: Campbell [ 38 ] claims that the experiencing of temporary negative welfare effects can be important to drive responses, which, in turn, improve welfare through motivating life-sustaining behaviors, and that the absolute eradication of all negative welfare effects is not therefore desirable; differently, Heimbürge et al showed that a wide array of stressors alter the cortisol concentrations in hair in many species [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It could be noted that in the literature, there is not always a clear correlation between stressors and poor welfare: Campbell [ 38 ] claims that the experiencing of temporary negative welfare effects can be important to drive responses, which, in turn, improve welfare through motivating life-sustaining behaviors, and that the absolute eradication of all negative welfare effects is not therefore desirable; differently, Heimbürge et al showed that a wide array of stressors alter the cortisol concentrations in hair in many species [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The social licence to use horses in competition is increasingly being questioned [ 64 , 65 , 66 , 67 , 68 ]. The overall low median RHpE score observed in the current study supports the continuing use of horses in affiliated eventing.…”
Section: Discussionmentioning
confidence: 99%
“…When deciding which stakeholders are most appropriate for use in a formal welfare assessment tool, researchers should consider all team members, not just the rider. However, in doing so, it is important to note that those stakeholders may also be influenced by the competitive environment and resultant complex ethical dilemmas [ 21 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate discussion amongst stakeholders where there is conflict between the needs of the horse and the demands of competition, a scale of priorities for maintaining (and improving) equine welfare would be a useful point of reference. Welfare priorities within the general equine sector have been identified [ 58 ], and the current development of an ethical framework to help stakeholders make decisions about what should or should not be done in specific situations will be invaluable [ 55 ].…”
Section: Discussionmentioning
confidence: 99%